Confirmatory Trials in the Evaluation of Anticancer Medicinal Products in Man—PFS2: A Measure of Therapeutic Action-At-A-Distance - Bryan Oronsky; Corey A. Carter; Tony R. Reid; Jan Scicinski; Arnold Oronsky; Michelle Lybeck; Scott Caroen; Meaghan Stirn; Neil Oronsky; Peter Langecker (Neoplasia: An International Journal for Oncology Research, 2015)
Overall survival (OS) has emerged as the definitive regulatory “be-all, end-all” for the demonstration of benefit in cancer clinical trials. The reason and the rationale for why this is so are easily appreciated: literally a “test of time,” OS is a seemingly unambiguous, agenda-free end point, independent of bias-prone variables such as the frequency and methods of assessment, clinical evaluation, and the definition of progression. However, by general consensus, OS is an imperfect end point for several reasons: First, it may often be impractical because of the length, cost, and the size of clinical trials. Second, OS captures the impact of subsequent therapies, both beneficial (i.e., active) and detrimental, on survival but it does not take into account the contribution of subsequent therapies by treatment arm; the postprogression period is treated as an unknown black box (no information about the potential influence of next-line therapies on the outcome) under the implicit assumption that the clinical trial treatment is the only clinical variable that matters: what OS explicitly measures is the destination, that is, the elapsed time between the date of randomization (or intention to treat) and the date of death, not the journey, that is, what transpires in-between. In long-term maintenance strategies, patients receive treatment in temporally separated but mutually interdependent and causally linked sequences that exert a “field of influence” akin to action-at-a-distance forces like gravity, electricity, and magnetism on both the tumor and each other. Hence, in this setting, a new end point, PFS2, is required to measure this field of influence. This article reviews the definition and use in clinical trials of PFS2 and makes the case for its potential applicability as a preferred end point to measure the mutual influence of individual regimens in long-term maintenance strategies with resensitizing agents in particular.